2002
DOI: 10.1210/me.2002-0100
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal Dysfunction Initiated by the Expression of Simian Virus 40 T-Antigen Leads to Angulated Sperm Flagella and Infertility in Transgenic Mice

Abstract: We have generated two transgenic mouse lines (GPX5-Tag1 and GPX5-Tag2) by expressing the Simian virus 40 large and small T-antigens under a 5-kb promoter of the murine glutathione peroxidase 5 (GPX5) gene. In GPX5-Tag1 mice, with a high level of T-antigen expression, severe dysplasia was found in the epididymis and seminal vesicles. These mice also developed adrenal and prostate tumors, and spermatogenesis was disrupted. In GPX5-Tag2 mice, with a lower level of T-antigen expression, the only histological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
2
30
0
1
Order By: Relevance
“…A similar phenotype was also observed in two other animal models: Ros1 knockouts (3) and glutathione peroxidase 5 (Gpx5)-TAG2 transgenic mice, the latter of which expressed Simian virus 40 small T-antigen driven by Gpx5 promoter (25). The histological changes of the initial segment of all three models were similar but not identical.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…A similar phenotype was also observed in two other animal models: Ros1 knockouts (3) and glutathione peroxidase 5 (Gpx5)-TAG2 transgenic mice, the latter of which expressed Simian virus 40 small T-antigen driven by Gpx5 promoter (25). The histological changes of the initial segment of all three models were similar but not identical.…”
Section: Discussionsupporting
confidence: 66%
“…The histological changes of the initial segment of all three models were similar but not identical. In Ros1 knockouts, the epithelium failed to undergo prepubertal differentiation (3), whereas the epithelium of Gpx5-TAG2 mice was slightly hyperplastic (25). In the present study, epithelial hypertrophy was observed.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…Evidence that transformed cells experience dormancy in the epididymis is provided by reports of the resistance of the epididymis to tumourigenesis, when other organs succumb, in response to the imposition of tumourigenic challenges, whether they be oncogene activation, downregulation of regulators or overexpression of growth factors: (i) in vivo activation of c-erbB-2 (the human homologue of cneu) leads to preneoplastic tumours in the kidney and lung, yet only hyperplasia and hypertrophy in the epididymis; 100 (ii) activation of cneu itself, 101 and of Notch-related int-3, 102 also lead only to epididymal hyperplasia in animals that develop mammary adenocarcinoma; (iii) activation of H-ras produces only epididymal hyperplasia in animals that develop hepatocarcinoma and polycystic kidney disease; 103 (iv) constitutive expression of stabilized b-catenin leads to hyperplasia in both epididymis and prostate, but only to transdifferentiation in the latter; 104 (v) silencing the p53 gene induces only hyperplasia in the epididymis of mice that develop other tissue cancers; 84 (vi) targeting the simian virus 40 large T antigen to the caput epididymidis results in the GPX5Tag-1 line to full tumours in the prostate but only nonmalignant hyperplasia and dysplasia of the epididymis; 105 (vii) overexpressing transforming growth factor alpha (TGF-a) leads to hyperplasia of p63-positive basal cells in the prostate but not in the epididymis; 106 and (viii) overexpressing vascular endothelial growth factor (VEGF) leads to epididymal hyperplasia without malignancy. 107 All these experimental models indicate that while the epididymis may succumb to unregulated proliferation, the resulting hyperplastic tissue is prevented from further development into tumours, which could represent a condition of dormancy ( Figure 3).…”
Section: Dormancy Of Early Tumour Cellsmentioning
confidence: 99%